Evaluation of a cleaner de-icing production of bituminous material blending with graphene by electrothermal energy conversion. (20th November 2020) - Xie, Xin-Ming; Su, Jun-Feng; Guo, Yan-Dong; Wang, Li-Qing
Abstract: De-icing of pavement is essential for road traffic safety and road maintenance. The addition of graphene can endow bituminous material with electrical conductivity. The aim of this work is to evaluate a cleaner de-icing production of bituminous material blending with graphene by electrothermal energy conversion. The dispersion state of different amount of graphene in bitumen was investigated. Electrical resistivity values of bitumen samples decreased sharply with the increase in the amount of graphene addition. The graphene/bitumen sample has a resistivity of 0.87 × 10 −2  Ω m when the amount of graphene added is 3.0 wt%. Thermal conductivity values of bitumen samples were measured and infrared thermographs of bitumen samples were used to prove the enhancement of thermal transmission in bitumen with the additive of graphene. The surface temperature of the bitumen samples blending with graphene can reach 39.3 °C when the voltage is greater than 50 V. The surface de-icing capability was evaluated by comparing ice shear force values of graphene/bitumen samples under direct current voltages. It was found that with only 0.5% graphene can realize the electrothermal de-icing purpose. These results prove the feasibility of this de-icing method using appropriate quantity of graphene. Graphical abstract: Infrared thermographs of graphene/bitumen samples under various direct current voltages (10–30 V) during time of 5, 10, 20, 30 and 40 s, (a1 -e1 ) 10 V, (a2 -e2 ) 20 V, and (a3 -e3 ) 30 V. Image 1 Highlights: Graphene is applied to realize the surface de-icing of bitumen. Graphene forms conductive current in bitumen. Electrical power can be converted into heat in bitumen. Heat helps to reduce the surface ice shear force of graphene/bitumen nanocomposites.